Devising chemically robust and cationic Ni(II)-MOF with nitrogen-rich micropores for moisture-tolerant CO2 capture: highly regenerative and ultrafast colorimetric sensor for TNP and multiple Oxo-anions in water with theoretical revelation - Goswami, Ranadip; Seal, Nilanjan; Dash, Soumya Ranjan; Tyagi, Anshu; Neogi, Subhadip (ACS Applied Materials & Interfaces, 2019)
Metal-organic frameworks (MOFs) show distinctive superiority for carbon dioxide (CO2) capture and luminescent sensing of toxic pollutants over other materials where combination of both of these properties together with improvement of hydrolytic stability and pore functionality is critical to environmental remediation applications. The Ni(II) framework [Ni-2(mu 2OH)(azdc)(tpim)](NO3)center dot 6DMA center dot 6MeOH (CSMCRI-3) (tpim = 44'4(2)-(1H-imidazole-245-triyl)tripyridine H(2)azdc = azobenzene-44'-dicarboxylic acid DMA = dimethylacetamide CSMCRI = Central Salt & Marine Chemicals Research Institute) encompassing cationic [Ni-2(mu(2)-OH)(CO2)(2)] SBUs is solvothermally synthesized from nitrogen-rich and highly fluorescent organic struts. The noninterpenetrated structure containing free nitrogen atom affixed microporous channels is stable in diverse organic solvents and weakly basic and acidic aqueous solutions. The activated MOF (3a) exhibits strong CO2-framework interaction and extremely selective CO2 adsorption over N-2 (292.5) and CH4 (11.7). Importantly water vapor exposure does not affect the surface area and/or multiple CO2 uptake-release cycles signifying potential of the porous structure for long-term use under humid conditions. Aqueous-phase sensing studies illustrate extremely specific and ultrafast detection of explosive 246-trinitrophenol (TNP) via remarkable fluorescence quenching (K-SV = 1.3 x 10 (5) M-1) with a 0.25 ppm limit of detection (LOD). Furthermore 3a serves as unique luminescent probe for highly discriminative and quick responsive detection of three noxious oxo-anions (Cr2O7 (2-) CrO4 (2-) MnO4-) in water via noteworthy turn-off responses and extreme low LODs (Cr2O7 (2-) 0.9; CrO4 (2-) 0.29; MnO4- 0.25 ppm). It is imperative to stress the outstanding reusability of the MOF toward multicyclic sensing of all four major water contaminants alongside visible colorimetric changes upon individual analyte detection. Mechanistic insights in light of the electron transfer route together with density functional theory calculations portray the influence of pore functionalization in framework-analyte interactions including alternation in energy levels where varying degrees of contribution of energy transfer explicitly authenticates high quenching of the material.
Keywords: chemically robust cationic MOF; DFT calculation; fast responsive detection; humid CO2 capture; TNP and oxo-anion sensing